On the challenges of making a sustainable kitchen: experimenting with sustainable food principles for restaurants - Matheus Alves Zanella (Research in Hospitality Management, 2020)
Concerns with the sustainability of food have moved from the margins of the gastronomy world to a much more central stage, mirroring a growing concern by citizens around food origins, carbon footprint and social practices in value chains. Evolving literature on food sustainability addresses many of these challenges, with macro and systemic approaches that have proved valuable in certain domains, such as food policy. However, professionals from the hospitality industry are still very under-informed on the methods adopted by researchers investigating food sustainability. This article tries to fill this gap by presenting an approach on how micro-level practices in restaurant kitchens can be informed by sustainable principles derived from the conceptual lens of food sustainability. It demonstrates the identification of principles and the definition of sustainable practices with two empirical cases: Hermann’s restaurant in Berlin, and Mesa pra Doze gastronomic project, in Brasília. Comparing those two different experiences, similar and dissimilar challenges were found. Contrary to common thinking, the higher costs normally associated with sustainable sourcing were diluted by the higher margins and low weight of sustainable ingredients in the total operational costs. Access to these, in terms of time and availability, proved to be the real challenge, given their less developed distribution channels. Lastly, the high degree of freedom and meaningful deliberation which the kitchen team benefited from, in both cases opened the possibility to more coherent and comprehensive definitions of sustainable principles and practices.